Comparison of sight reading dificulties for violin and piano / Glenn Suinggi - Suinggi, Glenn (2013)
Sight reading has been a very important skill to all musicians throughout the early days of music history (Reel, 2007). Throughout the baroque period, classical period, romantic period, the twentieth century, and the now, sight reading had been utilized in music making, whether it is during practice time or concerts. Until now, sight reading is still being utilized by all musicians. But what is sight reading actually? Sight reading is a skill to play music straight from the written music notations with the right sound and with the least mistakes. It is possible to be become well in sight reading (Lehmann & McArthur, 2002). Sight reading is very important because it is useful in some situations. For instance, in an audition, when the judge ask you to sight read a few parts from any repertoires, then this is when sight read is very useful where you could show your skills (Reel, 2007). Sight reading is also important during the musical instrument examination, when sight read can determine the marks (Lehmann & Mcarthur, 2002). In an orchestra, when there are new repertoires that are being played then everyone need to sight read it, so, sight reading is very important in this situation. But in the orchestra, when there is a new repertoire to be sight read, all the instruments will sight read simultaneously. However, all these instruments require different level of skills and techniques in order to be able to sight read.